Digitalized Learning Module in Cookery for Grade 11 Students - Palomeras, Patrick A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study focused on the development and evaluation of the Digitalized Learning Module in Cookery for Grade 11 Students of a public national high school in Antipolo City for the third quarter of the school year 2022-2023. In this study, weighted mean was utilized to ascertain how well the created digitalized learning module in cookery for Grade 11 students was received by instructors and expert responses. Independent-samples z Test was utilized to determine whether there was a statistically significant difference between the two sets of respondents' assessments of the created digitalized learning module in cookery for Grade 11 students. The study involved 30 respondents to complete the research investigation. It was revealed that both the TLE/TVL experts and TLE/TVL teachers agreed that the use of Digitalized Learning Module in Cookery among Grade 11 Students and its evaluation received very satisfactory ratings across multiple quality dimensions. Further, adopting a Digitalized Learning Module in Cookery for Grade 11 students can help improve their academic performance even when learning online. The Digitalized Learning Module may be a very useful tool to facilitate teaching Cookery for Grade 11 TVL class that could prepare students to develop critical thinking which may lead to higher academic performance in the subject. The use of the strategy is recommended for further research and may be applied to other subjects.